Application of Lean Six Sigma methodology to reduce the cycle time of out-patient department service in a rural hospital. (1st January 2014) - Bhat, Shreeranga; Jnanesh, N.A.
This article discusses the implementation of Lean Six Sigma (LSS) methodology in decreasing cycle time of out-patient department service of a rural hospital. The lean principles and Six Sigma define, measure, analyse, improve, and control process (DMAIC) approaches have been used to achieve this result. This article explains the step-by-step approach of LSS implementation in a rural Indian hospital for quality improvement and timely service to the community. This resulted in decreased cycle time of the process from 4.27 minutes to 1.5 minutes. Owing to the project a 97% reduction in average waiting time in the system and 91% decreases in queue length were reported. During this study, data was collected on all possible causes. Statistical techniques and GEMBA were used to analyse the data. Based on analysis conclusions were made. Lean tools such as kanban, 5S, ergonomic design of work place, etc., were effectively used to improve process and sustain the process.